2019–2020 Florida Citrus Production Guide: Citrus Canker - Megan M. Dewdney; Evan G. Johnson; James H. Graham (EDIS, 2019)
Citrus canker is a leaf-, fruit-, and stem-blemishing disease that affects most citrus. Severe infections can cause significant fruit drop. It is caused by the bacterium Xanthomonas citri subsp. citri. Grapefruit, Mexican lime, and some early oranges are highly susceptible to canker. Lemons, limes, and Navel, Pineapple, and Hamlin oranges are moderately susceptible to canker. Mid-season oranges, Valencias, tangors, tangelos, and other tangerine hybrids are less susceptible, and tangerines are the least susceptible. This 6-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by M. M. Dewdney, E. G. Johnson, and J. H. Graham, and published by the Plant Pathology Department, March 2019.